Microeconomía - Vial, Bernardita; Zurita, Felipe, 1969- (Ediciones Universidad Católica de Chile, 2018)
Microeconomics is a social science that studies human behavior in relation to the consumption, production and exchange of goods, services and assets. This book progressively addresses the classic themes of the discipline, such as supply, demand and competitive equilibrium, then moving on to modern themes, such as uncertainty, game theory and information problems with their applications -oligopoly, agency theory, negotiation, adverse selection and signaling ". This expanded second edition delves into the classic topics of microeconomics and incorporates the critical theme of social welfare. Aimed at undergraduate students, Microeconomics gathers the experience of many years of the authors teaching courses in the area at the Pontificia Universidad Católica de Chile.